Code, Culture, and Concrete: Self-Driving Vehicles and the Rules of the Road - Tennant, Chris; Neels, Chris; Parkhurst, Graham; Jones, Peter; Mirza, Saba; Stilgoe, Jack (Frontiers in Sustainable Cities, 2021)
Behaviour on the road is ordered by a range of norms, rules, laws, and infrastructures. The introduction of self-driving vehicles onto the road opens a debate about the rules that should govern their actions and how these should be integrated with, or lead to the modification of, existing road rules. In this paper, we analyse the current rules of the road, with a particular focus on the UK's Highway Code, in order to inform future rulemaking. We consider the full range of laws, norms, infrastructures, and technologies that govern interactions on the road and where these came from. The rules have a long history and they contribute to a social order that privileges some modes of mobility over others, reinforcing a culture of automobility that shapes lives, livelihoods and places. The introduction of self-driving vehicles, and the digital code on which they depend, could reorder the culture and concrete of our roads, by flattening the multidimensional rules of the road, hardening rules that are currently soft and standardising across diverse contexts. Future rule changes to accommodate self-driving vehicles may enable increases in safety and accessibility, but the trade-offs demand democratic debate.